Fontes d’água: sítios históricos para pensar sobre o processo de formação do atual núcleo de moradia da comunidade quilombola de Galeão, Cairu (BA) - Almeida, Fabio Guaraldo; Campos, Sílvio (Brasiliana: Journal for Brazilian Studies, 2021)
This article discusses the history of the community Galeão quilombola during the post-abolition period (from 1888 onwards) when public policies of the Brazilian government neglected this increasingly influent and numerous black population, which was regarded as threatening the the white and Catholic image of society in the period. The new strategies used by quilombolas to widen their spaces of sociability and cultural visibility are not registered in books, and there are no known written narratives. In this sense, archaeology and oral history acquire a prominent place. Thus, the archaeology developed in the quilombola community of Galeão, on the coast of the state of Bahia, focuses on landscape archaeology to understand the sources and uses of water, as archaeological sites where activities and socialization of the population of African descent occurred, which helps to understand the process of formation of the current quilombola landscape of the community of Galeão.